Expectations vs Recognition: An Analysis of the Implementation of a Science Teacher Training Program in Designing Smartphone-Assisted Practicum Activities - Rizki Zakwandi; Alfiansah Sandion Prakoso; Ika Mustika Sari; Deden Saepuzaman; Dedi Sasmita (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study proposes to examine the implementation of a science teacher training program for developing smartphone-assisted practicums, emphasizing the correspondence between expectations and program outcomes. This research depends on the substantial findings regarding the application of smartphones in scientific studies, which remain primarily theoretical and have not been extensively adopted by teachers in schools. The training program consists of three primary phases: self-assessment for science teachers, assessment of school laboratories, and a workshop focused on the utilization of smartphones in experiments. The results indicated that participants responded positively to the training, with the program's achievement level varying from "achieved" to "highly achieved." Educators evaluated the material as pertinent, practical, and capable of enhancing comprehension and proficiency in the design of novel experiments. The reflection results indicated a necessity for additional training on complex practical subjects, including Electricity, Magnetism, Thermodynamics, and Fluids, with instruction in the construction of student worksheets and smartphone sensor-based data analysis. This course connects research findings with educational practices and promotes the transformation of technology-enhanced science learning in schools.